Peuples autochtones et patrimonialisation de la nature protégée : les San indésirables dans le « Central Kalahari » (Botswana) ? - Éric Glon; Anderson Chebanne (VertigO)
Co-management with indigenous people in nature conservation seems to be a paradigm in heritage processes but the Kalahari case in Botswana is on the opposite side from this trend. Most of these indigenous people are displaced from the CKGR to resettlement camp nearby. New Xade is one of them. Focusing on this case, we explain how the government deny hunter-gather lifestyle and settle San as wage laborers and farmers. Most of the San suffer from a rapid and violent settling process and ethnocide. An aboriginal territorial appropriation and a system of heritage values is replaced by heritage processes based upon new “tradeability” opportunities, like nature conservation tourism and diamonds reserves but local cultural differences between Bantu and San and political choices are also quite important.